The Law Enforcement Of Rehabilitation Sanctions Against Narcotics Users - Irsano Marthanova Erisky; Widayati Widayati (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to identify and analyze the enforcement of rehabilitation sanctions against narcotics users at the Central Java Regional Police and to identify and analyze the obstacles in law enforcement of rehabilitation sanctions against narcotics users at the Central Java Regional Police. This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used are primary and secondary data which will be analyzed qualitatively. The research problems were analyzed using the theory of justice and the theory of expediency. The results of the study conclude that looking at the criminal provisions of Article 127 paragraphs (2) and (3), it can be concluded that judges in deciding cases referred to in Article 127 paragraph (1) are required to pay attention to the articles that regulate rehabilitation provisions so that later addicts and victims Drug abusers can be rehabilitated. The obstacles that come from the government, it is stated that there are 5 (five) obstacles, namely: a) There has not been a special place for addicts and victims of narcotics abusers to rehabilitate, b) The problem of rehabilitation costs for convicts of abuse cases narcotics, c) There is no rehabilitation center appointed by the Government, d) There is a difference in information between the defendant, witnesses and the results of the criminalistic laboratory. e) An execution problem occurred.